Pendampingan Balita Stunting Dan Pra Stunting Di Kecamatan Jambangan Kota Surabaya - Wirdatun, Husna; Elvandari , Milliyantri (Journal Of Human And Education (JAHE), 2024)
Indonesia is a large archipelagic country and has many problems, especially those related to nutritional status. Stunting is a growth and development disorder in young children that causes disruption of linear growth from pregnancy to 24 months due to lack of nutritional intake. The aim of this community service activity is to provide assistance to target toddlers to achieve a reduction in the number of stunted and pre-stunting toddlers and improve the nutritional status of toddlers. The method used in community service activities involves visiting the homes of stunted and pre-stunting toddlers and monitoring anthropometric measurements on target toddlers every month. As a result of this service activity, the target toddlers experienced an increase in weight and height, although not statistically significant, so that giving PMT was proven to be effective in increasing the weight of toddlers. Based on the results of food recall calculations and interviews with mothers of toddlers, the majority of toddlers are targeted to consume very little food so that their nutritional intake is less than their needs.